Drying kinetics and moisture diffusivity study of ripe Jackfruit - Dash, K. K (2016)
This study presents the mathematical model of thin layer drying behavior of ripe jackfruit (Artocarpus heterophyllus). The experiment was conducted at four different temperatures i.e. 50, 60, 70 and 80°C using a tray dryer. At varying temperature the dry basis moisture content values were subsequently used to fit 14 different thin-layer drying empirical models and among all, Middilli et al. model was found to be most suitable model representing the drying behavior of jackfruit. The constants and coefficients of Middilli et al. model were correlated with temperature and an equation was developed to describe the drying kinetics of jackfruit at a given time-temperature combination. Fick’s second law of diffusion was used to characterize the effective diffusion of water molecules from the jackfruit pulp during the falling rate period drying process. The value of effective moisture diffusivity was found to increase with increase in temperature. From the analysis maximum diffusivity of 4.56 x 10-10 m²/sec was obtained at 80°C and minimum diffusivity of 1.264 x 10-10 m²/sec was obtained at 50°C. The effective moisture diffusivity was correlated with temperature by Arrhenius equation. The activation energy which is an indicator of minimum energy required to remove moisture from a solid matrix was found to be 40.846 kJ/mol. The pre exponential factor of Arrhenius equation was found to be 5 x 10-4 m2/s.